Industrial Relations and Personnel Mangement - Pylee, M.V.; George, Simon (New Delhi : Vikas Publishing House, 2007)
Business
Keywords: Industrial relations and personal management; Industrial Relations; Labour Relations; Industrial Manager; Personnel Manager; Trade Unions; Role of Foreman Personnel Management; Employment; Absenteeism in Industry; Welfare Services; Condition of Services; Employee Services; Conditions of Service; Retrenchment; Labour Legislation; Human Resource Development